Language Ideologies, Policies and Practices
XII, 268 p. 4 illus.
Keywords: The contributors to Language Ideologies, Policies and Practices investigate the workings of language ideologies in relation to other social processes in a globalizing world. They explore in detail the specific ways in which language ideologies underpin language policy and the relationship between public policies and individual practices. Particular attention is given to Europe, where the impetus to social transformation within and across national boundaries is in renewed tension with conflicting national and supra-national interests, with these tensions reflected in the complex issues of language choice and language policy.